Ascertainment of iron deficiency and depletion in blood donors through screening questions for pica and restless legs syndrome. Issue 8 (10th January 2013) - Bryant, Barbara J.; Yau, Yu Ying; Arceo, Sarah M.; Hopkins, Julie A.; Leitman, Susan F.
<x xml:space="preserve">Abstract</x> Background Pica and restless legs syndrome (RLS) are associated with iron depletion and deficiency. The presence of pica and RLS was prospectively assessed in blood donors. Study Design and Methods During a 39‐month period, 1236 donors deferred for fingerstick hemoglobin (Hb) level of less than 12.5 g/dL and 400 nondeferred "control" donors underwent health screening and laboratory testing (complete blood count, ferritin, iron, transferrin). Pica and RLS were assessed by direct questioning. Deferred donors and iron‐deficient control donors were given 325 mg of ferrous sulfate daily for 60 days. Reassessments were performed and additional iron tablets dispensed at subsequent visits. Results Pica was reported in 11% of donors with iron depletion or deficiency, compared with 4% of iron‐replete donors (p < 0.0001). Pagophagia (ice pica) was most common and often of extraordinary intensity. Female sex, younger age, and lower mean cell volume and transferrin saturation values were strongly associated with pica. Donors with pica given iron reported a marked reduction in the desire to consume the nonnutritive substance by Days 5 to 8 of therapy, with disappearance of symptoms by Days 10 to 14. RLS was reported in 16% of subjects with iron depletion or deficiency compared with 11% of iron‐replete donors (p = 0.012). Iron replacement generally resulted in improvement of RLS symptoms; however, at least 4 to 6 weeks of iron therapy was necessary. Conclusion The presence of pica is associated with a high probability of iron depletion or deficiency in blood donors; however, RLS lacks a strong correlation in this population. Screening questions for pagophagia may be useful in the ascertainment of iron deficiency in donors and may identify those who would benefit from oral iron.